Textos multimodais: ilustração ou interpretação? - DIAS, Valdete Pereira (2021)
Like verbal texts, visual texts also have specific structures in their construction. These specificities require literacy for the construction and reading of this text modality. This descriptive-analytical research aims to perform a qualitative analysis of reading and textual interpretation activities, composed by multimodal genres in three textbooks of Portuguese language. They are elaborated by different publishers, and used by students of the 3rd year of high school of public schools in the city of Abaetetuba-Pa. Our focus is to observe if the books collaborate for the visual literacy of the student, working the specificities required by this one. genre. Therefore, this work is encouraged by methodological theoretical assumptions of multimodality advocated by Kress and Van Leeuwen (1996, 2006). The relevance of studying the approach of multimodal texts in textbooks is given by the functionality that the textbook has, serving as subsidy for the teaching of Portuguese language, and also by the constant presence of this type of text in society, as well as in tests. selective. The research results indicate that the contribution of the three books analyzed for the learning and the development of the student's multimodal literacy is precarious, precisely due to the little explanation of this type of text.